Development and validation of a rapid and sensitive LC-MS/MS method for the determination of aripiprazole in human plasma: Application to a bioequivalence study - Patel, D. S.; Sharma, N.; Patel, M. C.; Patel, B. N.; Shrivastav, P. S.; Sanyal, M. (Acta chromatographica, 2014)
A rapid, selective, and sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) assay has been proposed for the determination of aripiprazole in human plasma. The analyte and propranolol as internal standard (IS) were extracted from 200 mu L of human plasma via liquid-liquid extraction using methyl tert-butyl ether under alkaline conditions. The best chromatographic separation was achieved on an Aquasil C18 (100 x 2.1 mm, 5 mu m) column using methanol-deionized water containing 2 mM ammonium trifluoroacetate and 0.02% formic acid (65:35, v/v) as the mobile phase under isocratic conditions. Detection of analyte and IS was done by tandem mass spectrometry, operating in positive ion and multiple reaction monitoring (MRM) acquisition mode. The method was fully validated for its selectivity, interference check, sensitivity, carryover check, linearity, precision and accuracy, reinjection reproducibility, recovery, matrix effect, ion suppression/enhancement, stability, ruggedness, and dilution integrity. The assay was linear over the concentration range of 0.10-100 ng mL super(-1) for aripiprazole. The intra-batch and inter-batch precision (%CV) was [< or =]4.8%, while the mean extraction recovery was >96% for aripiprazole across quality control levels. The method was successfully applied to a bioequivalence study of 10 mg aripiprazole orally disintegrating tablet formulation in 27 healthy Indian subjects under fasting and fed condition. The reproducibility in the measurement of study data was demonstrated by reanalysis of 260 incurred samples.